Sytuacja ludności pochodzenia rumuńskiego w rosyjskiej Besarabii. Na marginesie artykułu Nikołaja Durnowa "Z okazji stulecia przyłączenia Besarabii do Rosji (1912)" - Kubiak, Antoni P. (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
The author of this article presents the impact of Russian rule in Bessarabia on the local Orthodox Church, education and the identity of Moldovans. He based his reflection on Nikolai Nikolaevich Durnovo’s essay, published on 27 May 1912 in the Sankt Petersburg’s News [Rus. Санкт-Петербургские ведомости], entitled “On the Occasion of the Centenary of the Incorporation of Bessarabia into Russia” (1912), he translated from Russian himself.
p. 29-52
Summary in English and Russian.
Keywords: Bessarabia; Moldavia - history; Orthodox Church; Bănulescu-Bodoni, Gabriel (1746-1821); Durnovo, Nikolai Nikolaevich; Lebedyev, Pavel; Chichagov, Seraphim (1856-1937)